Glucose uptake by E-ory nanoemulsion in L6 Myotubes - Mohd Faez Bachok (2011, 2011)
The prevalence of type diabetes mellitus globally is expected to increase up to 366 million people by 2030 according to current accretion. Despite advancements in managing this disease and the many new drugs developed, it is still a problem and especially most of the drugs are associated with side effects. For that reason, efforts to search for alternative treatments for this disease had been conducted extensively in recent years, one of which is E-ORY. E-ORY is the product mixture of antioxidants such as gamma-oryzanol, tocopherol and tocotrienol in blended rice oil palm and palm oils. Advantages of nano-emulsion over conventional emulsion like higher solubility and bioavailability are our reasons for applying it onto E-ORY. Hence, to screen the capability of E-ORY nanoemulsion as a new potential for type 2 diabetes mellitus, we conducted a study the objective of which was investigate the glucose uptake of L6 myotubes in vitro. We investigated the glucose uptake on insulin stimulated L6 and non-insulin stimulated l6 myotubes in the presence and absence of treatment. For the treatment, 3 different concentration of E-ORY nanoemulsion (2000, 1000 and 500 ppm) were selected and metformin 10µM was used as control. E-ORY nanoemulsion used in this study is oil-in-water emulsion with mean diameter of 107.7 nm with zeta potential of -23.4 mV. From the experiments, insulin stimulated L6 cells gave significantly better results. Glucose uptake recorded for formal group was 84.39±21.55 dpm. The first concerntration of E-ORY tested on L6 cell was 500 ppm where the result obtained was 93.93±19.19 dpm, while 1000ppm E-ORY gave 102.13±7.45 dpm. The highest concerntration (2000ppm) of E-ORY nanoemulsion showed a glucose uptake of 123.70±18.75 dpm. For metformin, glucose uptake was recorded to be 124.78±22.77 dpm. On the other hand, results from non-stimulated L6 cells were non-consistent for the 3 concentrations of E-ORY nanoemulsions and failed to show improvements in glucose uptake. Overall, result obtained from the experiments show that E-ORY nanoemulsion was only able to improve the glucose uptake by L-6 muscle cell stimulated with insulin. Thence, E-ORY nanoemulsion may have the capability to improve glucose uptake among type diabetic patients.
Project paper (B.Sc.(Nutrition of Community Health)) - Universiti Putra Malaysia, 2011.